Investments in sexually transmitted infection research, 1997-2013: a systematic analysis of funding awarded to UK institutions - Michael G Head; Joseph R Fitchett; Jackie A Cassell; Rifat Atun (Edinburgh University Global Health Society, 2015)
We report the first study that analyses public and philanthropic investments awarded to UK institutions for research related to sexually transmitted infections (STIs). We systematically searched award data from the major funders for information on all infectious disease research funding awarded in 1997-2013. The STI-related projects were identified and categorised by pathogen, disease and type of science along the research pipeline from preclinical to translational research. We identified 7393 infection-related awards with total investment of GBP 3.5 billion. Of these, 1238 awards (16.7%) covering funding of GBP 719.1 million (20.5%) were for STI research. HIV as an STI received GBP 465 million across 719 studies; non-HIV STIs received GBP 139 million across 378 studies. The Medical Research Council provided greatest investment (GBP 193 million for HIV, GBP 45 million for non-HIV STIs). Preclinical awards totalled GBP 233 million (37.1%), whilst translational research received GBP 286 million (39.7%). Substantial proportions of HIV investment addressed global health research (GBP 265 million), vaccinology (GBP 110 million) and therapeutics (GBP 202 million). For other STIs, investments focused on diagnostics (GBP 45 million) and global health (GBP 27 million). Human Papilloma Virus research received GBP 58 million and chlamydia GBP 24 million. Funding for non-HIV STIs has declined in the three most recent years of this data set. Conclusions The investment for HIV research awarded to UK institutions correlates with the high global burden, but other STIs are relatively neglected, including gonorrhoea and syphilis. Future STI funding should be better aligned with burden while addressing the emerging risk of antimicrobial resistance in Neisseria gonorrhoeae and outbreaks of other pathogens.